Reduced orbitofrontal and temporal grey matter in a community sample of maltreated children. (10th August 2012) - De Brito, Stéphane A.; Viding, Essi; Sebastian, Catherine L.; Kelly, Philip A.; Mechelli, Andrea; Maris, Helen; McCrory, Eamon J.
<x xml:space="preserve">Abstract</x> Background: Childhood maltreatment is strongly associated with increased risk of psychiatric disorder. Previous neuroimaging studies have reported atypical neural structure in the orbitofrontal cortex, temporal lobe, amygdala, hippocampus and cerebellum in maltreated samples. It has been hypothesised that these structural differences may relate to increased psychiatric vulnerability. However, previous studies have typically recruited clinical samples with concurrent psychiatric disorders, or have poorly characterised the range of maltreatment experiences and levels of concurrent anxiety or depression, limiting the interpretation of the observed structural differences. Methods: We used voxel‐based morphometry to compare grey matter volume in a group of 18 children (mean age 12.01 years, SD = 1.4), referred to community social services, with documented and well‐characterised experiences of maltreatment at home and a group of 20 nonmaltreated children (mean age 12.6 years, SD = 1.3). Both groups were comparable on age, gender, cognitive ability, ethnicity and levels of anxiety, depression and posttraumatic stress symptoms. We examined five a priori regions of interest: the prefrontal cortex, temporal lobes, amygdala, hippocampus and cerebellum. Results: Maltreated children, compared to nonmaltreated peers, presented with reduced grey matter in the medial orbitofrontal cortex and the left middle temporal gyrus. Conclusions: The medial orbitofrontal cortex and the middle temporal gyrus have been implicated in reinforcement‐based decision‐making, emotion regulation and autobiographical memory, processes that are impaired in a number of psychiatric disorders associated with maltreatment. We speculate that grey matter disturbance in these regions in a community sample of maltreated children may represent a latent neurobiological risk factor for later psychopathology and heightened risk taking.